PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN PRESTASI BELAJAR IPS PADA SISWA SMPN 3 BUKIT KEMUNING - siti Nuryani (Universitas Muhammadiyah Kotabumi, 2022)
Social Sciences (IPS) is a subject that discusses problems/cases of how students live socially, as a nation and as a state. The learning process should ideally prioritize the active involvement of students in interacting with learning resources and materials. Students must always be trained to think critically to solve problems, cooperate and establish active communication between students and teachers as learning facilitators. One alternative learning that is currently becoming a phenomenal that is growing in the world of education is participatory learning. The principle of participatory learning is that students have learning needs, understand learning techniques and learn behavior. To achieve maximum learning outcomes, the author tries to change the learning method with discussion techniques. In this case the author uses the Jigsaw comparative learning model. The application of this discussion technique is a participatory learning technique, aimed at training students to communicate actively with fellow learners so that the learning environment becomes more lively and passionate. Apart from being a pillar/element in Contextual Teaching and Learning, the group discussion learning strategy is an alternative learning model that can be used to maximize student involvement through solving cases/problems that are in accordance with the basic competencies that must be mastered by students.